Gemcitabine-Induced Hemolytic Uremic Syndrome in Pancreatic Cancer: A Case Report and Review of the Literature - Lee, Hye Won (The Korean Society of Gastroenterology; the Korean Society of Gastrointestinal Endoscopy; the Korean Association for the Study of the Liver; the Korean Society of Neurogastroenterology and Motility; Korean Association for the Study of Intestinal Diseases; Korean College of Helicobacter and Upper Gastrointestinal Research; Korean Pancreatobiliary Association; Korean Society of Gastrointestinal Cancer, 2014)
Hemolytic uremic syndrome (HUS) is a rare thrombotic complication characterized by a triad of microangiopathic hemolytic anemia, thrombocytopenia, and acute renal failure. HUS may be caused by several different conditions, including infection, malignancy, and chemotherapeutic agents, such as mitomycin, cisplatin, and most recently, gemcitabine. The outcome of gemcitabine-induced HUS is poor, and the disease has a high mortality rate. This study reports a case of gemcitabine-induced HUS in a patient with pancreatic cancer in Korea.